IN KIND RESTITUTION IN SERBIA – GESTATION PERIOD - Samardžić, Stefan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
On the sixth day of the tenth month of the eleventh year of the twenty first century, sixty six years after the first confiscation of property after the Second World War, a new law on general restitution of property came to light in Serbia. This play with numbers and words, as the article itself, aims at drawing the attention of legal scholars to the problems surrounding restitution in Serbia within the limits set by the law. Our intention was to point out to the incompleteness and shallowness of the Law by offering a systematic analysis, supported by arguments, of legislation on which the Law on Restitution rests and to propose suggestions that would help overcome difficulties in interpreting certain provisions of the Law, ultimately stating what the law ought to be (de lege ferenda).